Measuring policy entitlements at the micro-level: maternity and parental leave in Europe. Issue 1 (1st January 2018) - Bártová, Alžběta; Emery, Tom
ABSTRACT: Comparative social policy analysis has been shaped by the measurement of policy as a macro phenomenon. However, social policy theories have consistently asserted that policy entitlements vary across class, gender, ethnicity and the life-course. This paper synthesises a number of innovations to produce an approach which allows researchers to explore the policy heterogeneity within populations, across populations and over time. Using the example of maternity and parental leave, policy entitlements are identified through the calculation of financial support an individual would receive if they were to have a child, using a combination of legislative rules with representative survey sample. The results reveal far greater heterogeneity in policy entitlements than existing indicators suggest, with considerable implications for research on maternity and parental leave. This approach is not limited to maternity and parental leave benefits and demonstrates a way to explore comparative social policy in greater depth and detail.